Power supply for a smart contact lens 1 - Zhang, Beibei (Nanyang Technological University, 2023)
In recent times, there has been a notable surge in the popularity of smart contact lenses. Regrettably, the matter of power supply for these advanced lenses has been somewhat neglected, consequently raising concerns about potential ocular harm in the event of an accidental rupture or leakage. As a resolution, our research endeavors focus on the development and assessment of a novel battery type, engineered to provide a secure and user-friendly energy source for smart contact lenses, even permitting surgical procedures in the presence of tears. To address this, we introduce a flexible and biocompatible aqueous battery tailored specifically for smart contact lenses. This innovative design incorporates a series of Prussian blue nanoparticle-shaped flexible electrodes serving as cathodes and anodes, enabling the power supply to operate optimally with sodium ions (Na+) and potassium ions (K+) without necessitating supplementary encapsulation. Moreover, this battery possesses sufficient capacity to sustain the operation of microprocessors in low-power modes, while its flexible composition maintains a consistent charging and discharging performance. The anode of the battery was composed of silver (Ag) and copper hexacyanoferrate (CuHCFe), meticulously chosen for their specific properties conducive to efficient power generation and utilization. The cathode, on the other hand, was seamlessly embedded within a UV light-polymerized hydrogel that forms the soft contact lens, featuring an intercalated lens cleaning paper that serves as an impermeable barrier for ions. Our experimentation protocol included cyclic voltammetry (CV) and galvanostatic cycling (GCPL) electrochemical assessments conducted in a simulated tear fluid environment using 1M sodium chloride. Additionally, to validate the operational efficacy of the battery, we utilized contact lens cleaning fluid, ensuring a secure power supply for forthcoming smart contact lenses while mitigating the potential risks associated with battery leaks or impairment.